PERBANDINGAN PENGGUNAAN MODEL PJBL DAN PBL TERHADAP PEMBELAJARAN SEJARAH KELAS XI DI SMA NEGERI 8 MUARO JAMBI - Hade Polani, Olan; Heidi Karmela, Siti; Agustiningsih, Nur (Universitas Batanghari Jambi, 2025)
The aim of the research is to find out whether there is a difference in the History learning outcomes of students using the PJBL and PBL learning methods and to find out the extent of the difference in student learning outcomes using the PJBL learning method and the PBL learning model. The method used in this research is the type of research the author uses is experimental research. Experimental research is research that is intended to determine whether or not there are comparisons in a case or subject being investigated. This research uses groups for treatment. While secondary sources used are books, theses, journals and internet sources. The research results provide an explanation where, from the results obtained in the research carried out in determining the comparison of PBL and PJBL methods and learning outcomes at SMAN 08 Muaro Jambi, the influence of learning using the PJBL method further increases interest in learning and learning outcomes. So it can be said that there is a significant comparison between variable X and variable Y so that it can be concluded that the value of the alternative hypothesis is accepted. And for learning outcomes in using the PJBL learning method, there were 30 students with the average student assessment results for the class getting a score of 78.66%.